Urgency of Licensing Restriction in Joint Venture Companies Related to TKDN - Pratama, Toebagus Galang Windi (Faculty of Law, Universitas Negeri Semarang, 2019)
Most companies that market their products in Indonesia in order to pass TKDN using the concept of Joint Venture agreements (PMA) often the parties working together are unbalanced in real terms the shares of foreign owners are greater than domestic shareholders. In such conditions the strong parties tend to impose their will on the weaker party. Therefore, according to the principle of freedom of contact in relation to the free market, in fully contracting is an affair of the parties, however legal protection and public interest are therefore required from government interference in the form of regulation or restrictions. The restrictions in regulating technology transfer from developed countries to developing countries aim to protect the interests of countries that divert technology because the inventor of the technology is considered to have made maximum efforts to find related technology but on the other hand the state is also obliged to protect and improve the welfare of its citizens from that, restrictions on patent licenses are needed so that the TKD is truly